Endoscope-Assisted Retrosigmoid Approach for Cerebellopontine Angle Epidermoid Tumor - Vaz-Guimaraes, Francisco; Gardner, Paul A.; Fernandez-Miranda, Juan C. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives Surgical resection is the only effective treatment modality for epidermoid tumors. Complete resection with preservation of neurological function must be pursued whenever possible, because it offers a cure for patients. However, the inability to identify hidden remnants, interdigitating around cranial nerves, especially in larger tumors, may be a contributing factor for incomplete resection. This operative video demonstrates the technical nuances in achieving complete resection of a cerebellopontine angle epidermoid tumor via an endoscope-assisted retrosigmoid approach.Design and Setting Operative video of an endoscope-assisted retrosigmoid, approach for complete resection of a cerebellopontine angle epidermoid tumor. The patient was a 16-year-old female, who presented with 1-year history of worsening headaches and imbalance. Her neurological exam was normal, including normal cranial nerve function, and hearing. Radiological evaluation revealed an epidermoid tumor in the right cerebellopontine angle, extending to the interpeduncular cistern. Surgical resection was recommended. Given extension of the tumor across the midline, an endoscope-assisted procedure was planned to increase the odds of complete resection.Results The video demonstrates the surgical technique applied for tumor resection. The patient's clinical symptoms resolved completely after surgery and she remained neurologically intact. Postoperative magnetic resonance imaging (MRI) confirmed complete tumor resection. There were no postoperative complications.Conclusions The use of endoscopic techniques for resection of cerebellopontine angle epidermoid tumor is safe and effective and may increase the odds of complete resection, especially in larger tumors spreading across the midline, by enabling the surgeon clear visualization of deep-seated and contralateral relevant neurovascular structures, not readily accessible by the surgical microscope.The link to the video can be found at: https://youtu.be/X6YP_7OeQQE.
Keywords: cerebellopontine angle; endoscope-assisted; epidermoid tumor; retrosigmoid approach